WAS THE COLONISATION OF AUSTRALIA AN INVASION OF SOVEREIGN TERRITORY? - Son, Rowan Nichol (Melbourne journal of international law, 2019)
This article presents a reassessment of the British colonisation of Australia from the internal perspective of the international law of the period. After a discussion of the value of using historical doctrine in this way, the article introduces three positions that might be taken on the peoples who were perceived as the least 'civilised' by Western international lawyers. These have not always been distinguished in the literature. The 'preclusive' position, according to which these peoples were incapable of sovereignty, is rejected as inconsistent with state practice. Although it does not prove feasible to eliminate either of the other two possibilities, the 'naturalist-legislative' and 'contractual' positions, they lead to similar results. On this basis it is concluded, not with complete certainty but with a high degree of confidence, that before colonisation the Aboriginal and Torres Strait Islander peoples of Australia were sovereign within their territories in the strict sense of international law. It is also concluded that describing colonisation as an 'invasion' of sovereign territory accords with the doctrinal language of the period. In these respects, historical international law, despite being shaped by and in the interests of Western colonisers, agrees with language used today by Aboriginal and Torres Strait Islander peoples. In the course of this reassessment, the article offers insights of broader application into the role of customary norms and the legal status of pre-colonial non-Western entities.